FSR 1716: a new Milky Way globular cluster confirmed using VVV RR Lyrae stars - Minniti, Dante; Dékány, István (Arxiv, 2017)
We use deep multi-epoch near-IR images of the VISTA Variables in the V\'ia L\'actea (VVV) Survey to search for RR Lyrae stars towards the Southern Galactic plane. Here we report the discovery of a group of RR Lyrae stars close together in VVV tile d025. Inspection of the VVV images and PSF photometry reveals that most of these stars are likely to belong to a globular cluster, that matches the position of the previously known star cluster FSR\,1716. The stellar density map of the field yields a $>100$ sigma detection for this candidate globular cluster, that is centered at equatorial coordinates $RA_{J2000}=$16:10:30.0, $DEC_{J2000}=-$53:44:56; and galactic coordinates $l=$329.77812,
Gesehen am 24.10.2017